Returning radiation in strong gravity around black holes: reverberation from the accretion disc. Issue 3 (24th August 2020) - Wilkins, D R; García, J A; Dauser, T; Fabian, A C
ABSTRACT: We study reflected X-ray emission that returns to the accretion disc in the strong gravitational fields around black holes using General Relativistic ray-tracing and radiative transfer calculations. Reflected X-rays that are produced when the inner regions of the disc are illuminated by the corona are subject to strong gravitational light bending, causing up to 47 per cent of the reflected emission to be returned to the disc around a rapidly spinning black hole, depending upon the scale height of the corona. The iron Kα line is enhanced relative to the continuum by 25 per cent, and the Compton hump by up to a factor of 3. Additional light traveltime between primary and secondary reflections increases the reverberation time lag measured in the iron K band by 49 per cent, while the soft X-ray lag is increased by 25 per cent and the Compton hump response time is increased by 60 per cent. Measured samples of X-ray reverberation lags are shown to be consistent with X-rays returning to the accretion disc in strong gravity. Understanding the effects of returning radiation is important in interpreting reverberation observations to probe black holes. Reflected X-rays returning to the disc can be uniquely identified by blueshifted returning iron K line photons that are Compton scattered from the inner disc, producing excess, delayed emission in the 3.5–4.5 keV energy range that will be detectable with forthcoming X-ray observatories, representing a unique test of General Relativity in the strong field limit.